The Effects of Differentiated Organic Fertilization on Tomato Production and Phenolic Content in Traditional and High-Yielding Varieties - Johana González-Coria; Julián Lozano-Castellón; Carolina Jaime-Rodríguez; Alexandra Olmo-Cunillera; Emily P. Laveriano-Santos; Maria Pérez; Rosa Mª Lamuela-Raventós; Jordi Puig; Anna Vallverdú-Queralt; Joan Romanyà (MDPI AG, 2022)
The challenge of sustainable agriculture is to increase yields and obtain higher quality products. Increased antioxidant compounds such as polyphenols in harvest products may be an added value for sustainable agriculture. The aim of the present study was to investigate whether three organic fertilization treatments with different levels of carbon and nitrogen, i.e., N-rich, N-rich+C, and N-poor+C, affected the phenolic content of different tomato varieties. The examined parameters were productivity, plant nutritional status, δ13C, and tomato phenolic content as an indication of the antioxidant capacity. The best production was obtained with 'Cornabel', a high-yielding Pebroter variety. The total phenolic content was highest in the traditional 'Cuban Pepper' variety regardless of treatment, while naringenin levels were high in all the Pebroter varieties. In N-poor+C fertilized plants, a lower N-NO3 content in leaves was correlated with higher levels of total polyphenols in the fruit. The high-water stress suffered by Montserrat varieties coincided with a low total phenolic content in the tomatoes. In conclusion, organic fertilization with reduced N did not influence the tomato yield but positively affected phenolic compound levels in varieties less sensitive to water stress.